How Leader Emotional Intelligence Shapes Employee Performance: The Dual Mediation of Individual Agility and Organizational Citizenship Behavior - Hari Gunawan; Suparto Wijoyo; Yetty Dwi Lestari; Muzakki Muzakki (Journal of Educational, Health and Community Psychology, 2026)
This study examines the impact of leader emotional intelligence (LEI) on employee performance (EP) in Indonesian public sector organizations, with individual agility (IA) and organizational citizenship behavior (OCB) tested as mediators. Using survey data from 467 civil servants across local government agencies (Organisasi Perangkat Daerah; OPD), the proposed structural model was analyzed with PLS-SEM. The results indicate that LEI has significant positive effects on EP, IA, and OCB. OCB significantly mediates the relationship between LEI and EP, whereas IA does not exhibit a significant mediating effect. These findings underscore the importance of strengthening emotionally intelligent leadership and cultivating environments that encourage OCB to enhance employee performance and public service outcomes. The study contributes by integrating LEI, IA, and OCB within a single empirical model in a public sector setting and by showing that OCB, rather than IA, is the more salient behavioral pathway linking leadership to performance. The findings also provide support for Social Exchange Theory by highlighting how relational quality and extra-role behaviors shape performance within bureaucratic contexts.